Media Edukasi Booklet Meningkatkan Ketrampilan Pemeriksaan Payudara Sendiri (Sadari) pada Kader Kesehatan: Booklet Education Media Improves Breast Self-Examination (BSE) Skills in Health Cadres - Sumiyati, Sumiyati; Widiastuti, Anita; Kurniasih, Hesti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Early detection of breast cancer is breast self-examination or BSE. Early detection is very important in reducing the death rate due to breast cancer. There are still health cadres who do not understand the correct method or steps for breast self-examination. Forms of public health services in preventing breast cancer through promotional efforts. Promotive efforts through health education with booklets as educational media have been used to improve self-breast examination skills for cadres. Community service activities aim to improve cadres' skills in the practice of self-breast examination and disseminate information to the public, especially women of childbearing age. The method involved lectures, discussions, demonstrations and re-demonstrations of the steps for breast self-examination which were attended by 24 cadres and the media used were booklets. Participants carrying out the redemonstration were divided into 3 groups accompanied by 2 servants. Evaluation to determine the ability of cadres to practice breast self-examination. The results of community service show an increase in breast self-examination skills among cadres. Educational media with booklets can improve awareness skills for health cadres in Karangtengah Village District Baturaden.